Recent trends in animal source food production and consumption in Bangladesh and Myanmar, and their implications for nutrition - Belton, Ben; Farook, Sami; Scott, Jessica (WorldFish, 2022)
The presentation tackles the recent trends in animal source food production and consumption in Bangladesh and Myanmar, and their implications for nutrition. Results showed that there is: a declining supply and consumption of capture fish, static/declining red meat; highly unequal consumption of all animal-source foods (ASF) across income groups; and ASF (especially fish) make important contributions to nutrient intakes but still high levels of nutrient inadequacy.